"Wittgenstein, Frege and the Vienna Circle" - "Baker, Gordon" (Oxford, 1988)
Part I: Philosophy of Logic Introduction Section 1: Frege 1. The Science of logic 2. The elements of logical analysis 3. Thought and language Section 2: `Notes on Logic' 1. Initial insights 2. Early criticisms of Frege's philosophy of logic 3. Some presuppositions of Wittgenstein's criticisms Section 3: Tractatus Logico-Philosophicus 1. Continuity through change 2. `Logic is transcendental' 3. Criticisms of Frege Section 4: Wittgenstein: Later Reflections on Logic 1. Demolition and reconstruction 2. Logical constants and the propositions of logic 3. Frege reconsidered 4. Ils n'ont rien appris, ni rien oublie Part II: Varieties of Conventionalism Section 5: Early Conventionalism 1. The search for consistent empiricism 2. The roots of logical empiricism: Hilbert and Poincare 3. Early logical empiricism: Schlick's conventionalism Section 6: The Conventionalism of the Vienna Circle 1. The influence of the `Tractatus' 2. Mature logical empiricism Section 7: Wittgenstein and Consistent Conventionalism 1. Philosophical typology 2. The dark side of the `Tractatus' 3. Later Wittgenstein: grammar and necessity Index.
Keywords: "Wittgenstein, Ludwig"